2012
DOI: 10.1111/j.1438-8677.2012.00667.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating contemporary pollen dispersal in two common grassland species Ranunculus bulbosus L. (Ranunculaceae) and Trifolium montanum L. (Fabaceae) using an experimental approach

Abstract: Pollen flow is a key biological process that connects plant populations, preventing genetic impoverishment and inbreeding. Pollen-mediated long-distance dispersal (LDD) events are especially important for plant species in increasingly fragmented landscapes. Patterns of pollen dispersal were directly estimated and dispersal kernels modelled in an experimental population of Ranunculus bulbosus and Trifolium montanum to determine the potential for LDD. Eight and 11 microsatellite markers were used for R. bulbosus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 61 publications
2
15
0
Order By: Relevance
“…This pattern is consistent with a wealth of research indicating that although capable of travelling large distances (Hagler, Mueller, Teuber, Machtley, & Van Deynze, 2011), pollinators predominantly travel considerably shorter distances (Rader et al, 2011), remaining in localized resource patches (Pasquet et al, 2008). This results in a distance decay distribution of pollen movement (Matter, Kettle, Ghazoul, Hahn, & Pluess, 2013), suggesting that between block movement (>500 m) in this experiment would be minimal. In spatially genetically structured plant populations, reduced long-distance pollination events, particularly in florally rich habitats, will result in a higher frequency of mating between close relatives.…”
Section: Habitat Effects On Pollen Movementsupporting
confidence: 90%
“…This pattern is consistent with a wealth of research indicating that although capable of travelling large distances (Hagler, Mueller, Teuber, Machtley, & Van Deynze, 2011), pollinators predominantly travel considerably shorter distances (Rader et al, 2011), remaining in localized resource patches (Pasquet et al, 2008). This results in a distance decay distribution of pollen movement (Matter, Kettle, Ghazoul, Hahn, & Pluess, 2013), suggesting that between block movement (>500 m) in this experiment would be minimal. In spatially genetically structured plant populations, reduced long-distance pollination events, particularly in florally rich habitats, will result in a higher frequency of mating between close relatives.…”
Section: Habitat Effects On Pollen Movementsupporting
confidence: 90%
“…Although a similar pattern had been reported from anemophilous and entomophilous plants (e.g., Albaladejo et al, 2012;Goto et al, 2006;Matter et al, 2013;Nakanishi et al, 2012;Robledo-Arnuncio and Gil, 2005), our results suggested a highly leptokurtic distribution compared with other entomophilous genera such as pollen dispersal in A. mono, which implies that a considerable amount of long-distance dispersal occurred whereas shortdistance pollen transfer predominated might be attributable to a wide variety of the pollinator fauna. Although the visitors to A. mono flowers, such as small insects such as flies, hover flies and solitary bees are generally habitat-dependent and have narrow foraging ranges (Steffan-Dewenter et al, 2002), occasional visits by honey bees ) might contribute to long-distance pollen dispersal because they have a large foraging range (Visscher and Seeley, 1982).…”
Section: The Mating System Of a Monosupporting
confidence: 82%
“…The tail shape of the dispersal kernel (i.e., whether thin-or fat-tailed) affects the ultimate distribution of genetic diversity within and between populations. Some studies report that pollen dispersal kernels are fat-tailed in tree species (Austerlitz et al, 2004;Klein, Lavigne, & Gouyon, 2006;Matter, Kettle, Ghazoul, Hahn, & Pluess, 2013;Ramos, Dequigiovanni, Sebbenn et al, 2016;Saro et al, 2014).…”
Section: Gene Flow and Dispersal Patternsmentioning
confidence: 99%